Reconstruction of Urethral Strictures in Patients with a Long History of Blind Urethral Dilatation - Ignjatovic, Ivan M.; Stojkovic, Ivica; Basic, Dragoslav; Stankovic, Jablan; Potic, Milan; Dinic, Ljubomir (Urology Journal, 2014)
Abstract Purpose: To compare urethral reconstructions in patients after several years with or without blind urethral dilatation. Materials and Methods: A retrospective study of 107 patients with urethral reconstructions was performed. Sixty patients with a long history of blind urethral dilatation (group 1) were compared with 47 patients without prior dilatations (group 2). Results: The type of surgery planned according to urethrography and endoscopy findings was appropriate in 37/60 (61.6%) patients in group 1 and in 39/47 (83%) patients in group 2 (P < .03). Anastomotic repairs were more frequent among the patients in group 2 (P < .001). Eighty five out of 107 patients were available for the 24 months follow-up. The success rate was higher in group 2 (91.4%) than patients in group 1 (70%) (P < .04). The greatest improvement in symptoms and quality of life occurred three months after the surgery (P < .05). Postoperative infection was persistent in 20/107 (18.7%) patients. Conclusion: Urethral strictures with a long history of blind dilatation are separate entity. They are more difficult to image, require more augmentation and staged procedures and have a lower success rate.